2022
DOI: 10.1038/s41591-022-01834-y
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions disrupting addiction map to a common human brain circuit

Abstract: Drug addiction is a public health crisis for which new treatments are urgently needed. In rare cases, regional brain damage can lead to addiction remission. These cases may be used to identify therapeutic targets for neuromodulation. We analyzed two cohorts of patients addicted to smoking at the time of focal brain damage (cohort 1 n = 67; cohort 2 n = 62). Lesion locations were mapped to a brain atlas and the brain network functionally connected to each lesion location was computed using human connectome data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 37 publications
(71 reference statements)
6
43
0
1
Order By: Relevance
“…Recent preclinical studies have demonstrated the potential of real-time fMRI-informed neurofeedback to modulate brain systems and circuits traditionally implicated in internalizing disorders [ 135 , 174 , 175 ] and suggest that the neurofeedback training success is associated with variations in regional GMV [ 176 ]. The efficacy of these interventions can benefit from the identification of robust and disorder-specific therapeutic targets from our comparative meta-analyses or other approaches (e.g., lesion network mapping [ 177 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical studies have demonstrated the potential of real-time fMRI-informed neurofeedback to modulate brain systems and circuits traditionally implicated in internalizing disorders [ 135 , 174 , 175 ] and suggest that the neurofeedback training success is associated with variations in regional GMV [ 176 ]. The efficacy of these interventions can benefit from the identification of robust and disorder-specific therapeutic targets from our comparative meta-analyses or other approaches (e.g., lesion network mapping [ 177 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Outcome variability in focal neuromodulation studies might reflect a host of factors, including suboptimal stimulation targets, and functional neuroimaging (e.g., resting-state fMRI) may yet play a role in assessing target selection and engagement in individual patients (Cash et al, 2021;Cole et al, 2020Cole et al, , 2022Fitzgerald, 2021;Fox et al, 2012;Nord et al, 2019;Price et al, 2021;Siddiqi et al, 2021a;Weigand et al, 2018;Weissman and Daskalakis, 2022). Furthermore, neuroimaging-based techniques such as lesion network mapping show promise in identifying new anatomical targets that are causally implicated in therapeutic change (Joutsa et al, 2022;Siddiqi et al, 2020Siddiqi et al, , 2021bSiddiqi et al, , 2022. Nevertheless, it remains the case that mappings between neuroanatomical loci and psychiatric diagnoses or symptoms have remained elusive.…”
Section: Functional Localizationmentioning
confidence: 99%
“…These findings may have important clinical implications given that the identification of effective treatment targets for addiction disorders has been exceptionally challenging, resulting in numerous neuromodulation trials with no consensus regarding the optimal targets [33]. Independent of the LNM study by Joutsa et al [30 ▪ ], two recently published large trials (one to facilitate smoking cessation, one to reduce craving in alcoholism) reported positive results with specific coil designs [34,35]. Although these studies did not intend to target the regions identified using LNM, the peaks of these coil electric fields overlapped remarkably well with the cortical network peak of the addiction remission network, demonstrating the potential therapeutic relevance of mapping brain circuits from beneficial brain lesions.…”
Section: Linking Lesion Network Mapping Findings To Treatment Targetsmentioning
confidence: 99%
“…In addition, a recent study applied this approach to lesions improving addiction, and localized a brain circuit thought to mediate smoking addiction remission [30 ▪ ]. Specifically, lesions resulting in smoking addiction remission showed positive connectivity to the insula and paracingulate cortex, and negative connectivity to the medial prefrontal cortex.…”
Section: Linking Lesion Network Mapping Findings To Treatment Targetsmentioning
confidence: 99%